Implementing Insurance Billing in Local Health Department Sexually Transmitted Disease Clinics in Virginia, 2017. Issue 8 (August 2020) - McGee, Felencia; Carter, Ashley; Lafon, Emily; Chesson, Harrell
Abstract : Abstract: In 2017, the Virginia Department of Health implemented billing of insurance in local health department sexually transmitted disease clinics. We examined data collected by Virginia Department of Health related to clinic encounters, billing, and revenue from sexually transmitted disease clinics statewide. Implementing insurance billing created a new revenue stream for local health departments. Abstract : This paper describes the implementation of insurance billing in local health department sexually transmitted disease clinics in Virginia in 2017, before Medicaid expansion in 2019.